PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS VIII-A SMPN 10 CIBINONG - Wiwin Asrianti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The research I conducted aims to determine the effect of the use of learning media on the learning motivation of class VIII-A students of SMPN 10 Cibinong. This is done because there are still many students who do not understand learning which if only explained by the teacher and do not use equipment or other learning aids. Of course, the media that will be used here is modern learning media. The research method that I use is descriptive qualitative research, the research sample is taken from students of class VIII-A SMPN 10 Cibinong which includes 20 students, the instrument I use is a questionnaire. Method The results of this study indicate that there is a significant effect of the use of instructional media on motivation in class VIII-A students of SMPN 10 Cibinong.